Evaluation of urinary proteins in healty full-term neonates by SDS-PAGE - Snezhana Palchevska; Velibor Tasik; Petar Korneti; Georgi Shestakov; Svetlana Tsekovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2004)
The pattern of urinary proteins in healthy full-term neonates was examined by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), coupled with determination of few parameters related to urinary protein excretion. Twenty healthy full-term neonates were included in the investigation. Five urine samples from each subject were collected on days 3, 7, 14, 21 and 28 after birth. Determination of total proteins was performed using turbidimetric method with sulfosalicylic acid. Urinary creatinine concentration was determined by Jaffe method. Urinary proteins were separated by horizontal gradient SDS-PAGE according to Görg. The highest values for total urinary proteins and for protein/creatinine ratio were detected in urine samples excreted on days 3 and 7 after birth. Three types of SDS-PAG electrophoretic profiles were observed. The first type of electrophoretic profile was characterized by the presence of proteins of mixed glomerular and tubular origin with molecular weights from 10 to 160 kDa. Typical for the second type of electrophoretic profile was the presence of two faint fractions with molecular weights of 78 and 90 kDa and several intensive low molecular weight fractions (14-67 kDa). In the third type of electrophoretic profile only low molecular weight proteins (10-67 kDa) were detected in all five urine samples. These findings express the transitory immaturity of the glomerular filter and tubular protein reabsorbing system of the newborn kidney. Apparently, the tubular protein handling normalizes later than the glomerular filtration of proteins